Relationship between spiritual intelligence and existential satisfaction with paranormal experience - Parra, Alejandro (2020)
The aim of this study is to assess the frequency of paranormal experiences and their relationship with the levels of spiritual intelligence and existential satisfaction. Three instruments were administered to a sample of 200 male and female participants: the Paranormal Experiences Survey, the Spiritual Intelligence Self Report Inventory and the Existential Satisfaction Scale. The results show that survey respondents had at least one of these experiences, and that spiritual intelligence is a strong predictor of them. The relationship with existential satisfaction was also significant. These experiences result in a feeling of spiritual satisfaction, thus suggestingthat they can generate positive effects and—far from being disturbing—contribute to the individual's ability to solve meaning and existential value issues. In conclusion, spiritual intelligence could be more adaptive for those who seek a meaning for their paranormal experiences, i.e., for those people who practice yoga or meditation, recall dreams, have a mental life richer in fantasy, and share a broader context of meaning in the face of the experiences of their spiritual lifestyle: a form of “evidence” that confirms the sense of their religious or spiritual practices, and that can be seen as an indicator that shapes or reaffirms the consistency between their spiritual practices.